Training on Goal Setting: Reducing Academic Procrastination - Sulistiyana Sulistiyana; Muhammad Arsyad; Eva Nurmaulida; Wiwik Widyanti (Universitas Lambung Mangkurat, 2024)
Generation Z individuals are in their teenage years. The problem of academic procrastination among female students in junior high schools belonging to Generation Z is in the high category. This service aims to reduce students' academic procrastination. The method used to achieve the goal is the goal-setting training method. The service subjects were 17 SMP Negeri 23 Banjarmasin students identified as experiencing academic procrastination in the high category based on the results of the Academic Procrastination Scale analysis. There was a decrease in academic procrastination after being given goal-setting training. Effective goal-setting training influences reducing procrastination among Generation Z teenagers in the city of Banjarmasin.